Perancangan Aplikasi Tata Usaha Kayu Dengan Traceability System Berbasis Web Pada PT Bumi Trikama Jayasri - Aprilia, Irma; Setiowati, Dewi (Universitas Muhammadiyah Riau, 2025)
PT Bumi Trikama Jayasri is a timber management company that faces challenges in recording timber distribution, such as data inaccuracies, delays in real-time input, and a lack of transparency in reporting. This research aims to design a web-based timber administration application with a traceability system that facilitates efficient recording, tracking, and reporting of timber distribution. The system development method uses the Waterfall model, consisting of analysis, design, implementation, testing, and maintenance stages. The technologies used include PHP with the Laravel framework and a MySQL database. The system is equipped with tracking features for distribution from TPN (Timber Collection Point) to barges, as well as reporting and data history modules. The Requirement Traceability Matrix (RTM) is used to verify the fulfillment of system requirements. Test results show that the system improves the efficiency and accuracy of record-keeping and supports faster and more accurate decision-making. This system is expected to serve as an effective digital solution for timber distribution management in the company.